Synthesis and modification of supports with an Alkylamine and their use in Albumin adsorption - Gomez, Cesar Gerardo (2008)
The morphological effect of polymeric networks (R) modified with terminal amino groups was studied on the adsorption of bovine serum albumin (BSA). Networks of ethylene glycol dimethacrylate and 2-hydroxyethyl methacrylate [poly (EGDMA-co-HEMA)] were synthesized by suspension polymerization, using different EGDMA contents and agitation speeds. These matrices were characterized by FTIR, mercury intrusion porosimetry, SEM, and swelling degree. The increase of the EGDMA concentration led to the formation of networks with the highest crosslinking degree and porosity. An earlier phase separation yielded a higher aggregation of rigid microspheres, also forming stable pore systems. The increase in coalescence frequency, together with the impeller speed, and the decrease of the stabilizer molecules led to an increment in drop size. Large fused aggregates of microspheres were formed with additional loss of small pores as the stirring was increased, attaining also a higher pore volume (Vp) and a slight decrease of the surface area. Once characterized, networks were activated with butanediolglycidyl ether (BDGE), and then reacted with hexamethylenediamine (HMDA) through coupling reaction. Only the RBDGE- HMDA networks synthesized with the highest EGDMA content and agitation speed showed BSA adsorption. Their base matrices exhibited a Vp higher than 1.4 mL/g, which allows easier protein diffusion into the support.